REALISTIC CORRECT SYSTEMS IMPLEMENTATION - Goerigk, W. (PROBLEMS IN PROGRAMMING, 2015)
The present article and the forthcoming second part on Trusted Compiler Implementation address correct construction and functioning of large computer based systems. In view of so many annoying and dangerous system misbehaviors we ask: Can informaticians righteously be accounted for incorrectness of systems, will they be able to justify systems to work correctly as intended? We understand the word justification in the sense: design of computer based systems, formulation of mathematical models of information flows, and construction of controlling software are to be such that the expected system effects, the absence of internal failures, and the robustness towards misuses and malicious external attacks are foreseeable as logical consequences of the models.